Organizational Immunity and its Role in Achieving the Strategic Entrepreneurship in Secondary Schools in the Southern Governorates of Palestine - Abu Borhom, Mohammed Ibrahim (Journal of Educational and Psychological Sciences, 2022)
The study aimed to verify the presence of the effect of Organizational Immunity as in Strategic Entrepreneurship in Secondary Schools in the Southern Governorates of Palestine, The study followed the Descriptive analytical approach and the questionnaire was the main data collection tool and it was applied to the study population which consists of secondary school teachers in the southern governorates of Palestine. The sample included (355) secondary school teachers, representing (7.5%) of the size of the study population. have been selected randomly with stratified sample way, and the study reached the most important results: The estimation of study sample for the degree of availability of organizational immunity in secondary schools in the southern governorates of Palestine from the teachers’ point of view, got a relative weight of (76.52%) which was high.The estimation of study sample for the degree of availability of strategic entrepreneurship in secondary schools in the southern governorates of Palestine from the teachers’ point of view, got a relative weight of (75.70%) which was high.There is a statistically significant relationship between organizational immunity and achieving strategic entrepreneurship in secondary schools in the southern governorates of Palestine, where the correlation coefficient reached (0.727). The most important recommendations of the study were: Increasing interest in promoting all elements of the organizational immunity in Secondary Schools through developing a culture of organizational immunity in them, which contributes to achieving the strategic entrepreneurship. That the school administration in Schools pay attention to the topic of strategic entrepreneurship.and the means leading to that, including caring for highly qualified teachers, investing their abilities and potentials, and providing them with the appropriate climate for development and creativity.